2009
DOI: 10.5539/ijbm.v3n12p106
|View full text |Cite
|
Sign up to set email alerts
|

Key Antecedents of Organizational Citizenship Behavior (OCB) in the Banking Sector of Pakistan

Abstract: The study is focused on the effects of Altruism, Conscientiousness, and Civic Virtue (three of the antecedents of Organizational Citizenship Behavior -OCB) and their relationship with Organizational Citizenship Behavior (OCB) in the Banking Sector of Pakistan. As per previous studies it has been hypothesized that there exists a direct and significant relationship between the antecedents chosen and Organizational Citizenship Behavior (OCB). Results prove that all the above mentioned antecedents have significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 25 publications
6
29
0
8
Order By: Relevance
“…In the study conducted by Poyraz et al [31] on workers of 4-and 5-star thermal hotels at the city center of Afyonkarahisar, they concluded that interactional justice is more influential on organizational citizenship behavior than the distributive and procedural justice. Buluc [23] found a positive and significant relationship between perception of justice of academic personnel and their organizational citizenship behavior.…”
Section: Relationship Between Organizational Justice and Organizationmentioning
confidence: 95%
See 1 more Smart Citation
“…In the study conducted by Poyraz et al [31] on workers of 4-and 5-star thermal hotels at the city center of Afyonkarahisar, they concluded that interactional justice is more influential on organizational citizenship behavior than the distributive and procedural justice. Buluc [23] found a positive and significant relationship between perception of justice of academic personnel and their organizational citizenship behavior.…”
Section: Relationship Between Organizational Justice and Organizationmentioning
confidence: 95%
“…The social exchange theory considers the interpersonal social relations as a kind of resource exchange [23].…”
Section: Organizational Justicementioning
confidence: 99%
“…Organizational citizenship behavior is the actions and activities employees are carrying out in addition to the main task and duties (Bukhari, Ali, Shahzad, & Bashir, 2009). Darmawati, Hayati, and Herlina (2013) suggested that it is a behavior that exceeds and expands from the behavior required by the organization.…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%
“…The implication is that an OCB-encouraging factor in a given culture may not necessarily be an encouraging factor in another culture. Furthermore, Bukhari et al [5] argues that different geographical contexts have different culture, values, norms and environment which necessitate a separate study for better understanding of OCB [5]. As a result, this research work was targeted at investigating reasons for imperceptibility of OCB in Ethiopian context, particularly in Dire Dawa University, and contributing factors to foster OCB in the university.…”
Section: Introductionmentioning
confidence: 99%